Analytical Analysis of The Technology for Cleaning Wool Fiber from Small and Large Impurities - Qadam Jumaniyozov; Urozov Mustafokul; Kamola Rustamova; Shoxabbos Bozorov (Scientific Trends, 2024)
It was found that the supply mechanism of the traction-cleaning equipment used in enterprises is inconveniently made, which negatively affects the performance of the equipment, the quality of the fiber and causes a significant decrease in economic efficiency. Wool fiber traction-the most basic and complex construction of the cleaning equipment includes the supply mechanisms.